Spin-Seebeck effect and thermal colossal magnetoresistance in the narrowest zigzag graphene nanoribbons. (23rd March 2021) - Wu, Dan-Dan; Fu, Hua-Hua
Abstract: Device miniaturization and low-energy dissipation are two urgent requirements in future spintronics devices. The narrowest zigzag graphene nanoribbons (ZGNRs), which are composed of just two coupled carbon-atom chains connected with carbon tetragons, are promising candidates that meet both of the above requirements well. Using the first-principles calculations combined with non-equilibrium Green's function approach, thermal spin-dependent transport through this kind of narrow ZGNR is investigated, and several exotic thermal spin-resolved transport properties are uncovered: (i) when an external magnetic field is applied, the ZGNRs are transited from the intrinsic semiconducting to the metallic state, and the thermal colossal magnetoresistance effect occurs with order of magnitudes up to 10 4 at room temperature; (ii) the thermal spin-dependent currents display a thermal negative differential resistance effect, and a well-defined spin-Seebeck effect (SSE) together with a pure thermal spin current occurs; and (iii) under suitable device temperature settings, a nearly perfect spin-filtering effect occurs in these narrowest ZGNRs. The theoretical results not only uncover the narrowest nanoribbon structures to realize the SSE and other inspiring thermal spin transport features, but also push carbon-based material candidates towards thermoelectric conversion device applications.